An outreach intervention to implement evidence based practice in residential care: a randomized controlled trial [ISRCTN67855475] - Weller David; Halbert Julie; Rowett Debra; Whitehead Craig; Crotty Maria; Finucane Paul; Esterman Adrian (BMC, 2004)
Abstract Background The aim of this project was to assess whether outreach visits would improve the implementation of evidence based clinical practice in the area of falls reduction and stroke prevention in a residential care setting. Methods Twenty facilities took part in a randomized controlled trial with a seven month follow-up period. Two outreach visits were delivered by a pharmacist. At the first a summary of the relevant evidence was provided and at the second detailed audit information was provided about fall rates, psychotropic drug prescribing and stroke risk reduction practices (BP monitoring, aspirin and warfarin use) for the facility relevant to the physician. The effect of the interventions was determined via pre- and post-intervention case note audit. Outcomes included change in percentage patients at risk of falling who fell in a three month period prior to follow-up and changes in use of psychotropic medications. Chi-square tests, independent samples t-test, and logistic regression were used in the analysis. Results Data were available from case notes at baseline (n = 897) and seven months follow-up (n = 902), 452 residential care staff were surveyed and 121 physicians were involved with 61 receiving outreach visits. Pre-and post-intervention data were available for 715 participants. There were no differences between the intervention and control groups for the three month fall rate. We were unable to detect statistically significant differences between groups for the psychotropic drug use of the patients before or after the intervention. The exception was significantly greater use of "as required" antipsychotics in the intervention group compared with the control group after the pharmacy intervention (RR = 4.95; 95%CI 1.69-14.50). There was no statistically significant difference between groups for the numbers of patients "at risk of stroke" on aspirin at follow-up. Conclusions While the strategy was well received by the physicians involved, there was no change in prescribing patterns. Patient care in residential settings is complex and involves contributions from the patient's physician, family and residential care staff. The project highlights challenges of delivering evidence based care in a setting in which there is a paucity of well controlled trial evidence but where significant health outcomes can be attained.